THE IMPACT OF THE INTERNET ON THE MODERN ENGLISH LANGUAGE - Ismoilova Kamolaxon (Galaxy International Interdisciplinary Research Journal, 2022)
This article deals with today's most relevant and intense on the emerging internet linguistics and its several opinions about the influence of the internet on the English language. Besides, in the article, the initial meanings of words in the Internet world and their development stages are also given.